Ensiklopedia Masakan Jawa Sebagai Pelestarian Budaya Menggunakan CMS Wordpress - Krisfi Marantika; Ajeng Savitri Puspaningrum; Ade Surahman (Jurnal Media Jawadwipa, 2023)
There are various kinds of cultural diversity in Indonesia, one of which is traditional cuisine. Traditional specialties are food and drinks that are commonly consumed by certain communities, with a distinctive taste that is accepted by these communities. Traditional specialties are various types of processed foods typical of Indonesian regions which are a form of local community creativity in processing food ingredients, combining spices and adding cultural value to them which must be preserved. In cooking, both methods and raw materials are passed down from generation to generation continuously. Javanese cuisine is an attraction for tourists and travelers visiting Indonesia. In order for the traditional Javanese cuisine not to become extinct in the masses, of course it needs to be maintained and maintained as much as possible. Javanese traditional society has a habit of conveying advice indirectly. They use symbols or figures of speech. One such symbol is food. Unfortunately, many traditional Indonesian foods are currently not well known by the next generation, including traditional Javanese food. The creation of this system also generates and presents the information needed by respondents as shown in one of the aspects of testing the Delone and McLean models, namely Information Quality, where this aspect tests the quality of information from the content created by the author, with a score of 114 out of 5. respondents who filled out the questionnaire. That way the creation of this system can make it easier for people to find information, both recipes and video tutorials for making traditional Javanese dishes.